Progress Report on Phase Separation in Polymer Solutions. Issue 26 (11th March 2019) - Wang, Fei; Altschuh, Patrick; Ratke, Lorenz; Zhang, Haodong; Selzer, Michael; Nestler, Britta
Abstract: Polymeric porous media (PPM) are widely used as advanced materials, such as sound dampening foams, lithium‐ion batteries, stretchable sensors, and biofilters. The functionality, reliability, and durability of these materials have a strong dependence on the microstructural patterns of PPM. One underlying mechanism for the formation of porosity in PPM is phase separation, which engenders polymer‐rich and polymer‐poor (pore) phases. Herein, the phase separation in polymer solutions is discussed from two different aspects: diffusion and hydrodynamic effects. For phase separation governed by diffusion, two novel morphological transitions are reviewed: "cluster‐to‐percolation" and "percolation‐to‐droplets, " which are attributed to an effect that the polymer‐rich and the solvent‐rich phases reach the equilibrium states asynchronously. In the case dictated by hydrodynamics, a deterministic nature for the microstructural evolution during phase separation is scrutinized. The deterministic nature is caused by an interfacial‐tension‐gradient (solutal Marangoni force), which can lead to directional movement of droplets as well as hydrodynamic instabilities during phase separation. Abstract : Polymerization‐induced phase separation is a vital mechanism to engender polymeric porous media involving not only thermodynamics but also fluid dynamics. For diffusion‐controlled evolution, an asynchronous effect of the polymer‐rich and the polymer‐lean phases toward equilibrium is discussed. For convection‐governed growth, an overview of deterministic motion of the polymeric droplets is presented. Characterization techniques of polymeric porous media are also elucidated.